2005
DOI: 10.1111/j.1440-1746.2005.03891.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma homocysteine concentrations as a predictor of steatohepatitis in patients with non‐alcoholic fatty liver disease

Abstract: The plasma homocysteine concentrations were significantly higher in patients with non-alcoholic fatty liver disease, while the concentrations were not affected by chronic viral hepatitis. Plasma homocysteine is a parameter for discriminating steatohepatitis from simple steatosis. Determining the plasma homocysteine concentrations may facilitate selection of steatosis patients in whom a liver biopsy should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 29 publications
(29 reference statements)
4
86
1
3
Order By: Relevance
“…Taken together, the results suggest that the changes in the level of PS in the liver 47 as well as the relative increase in the homocysteine blood level 49 is caused by decreased level of endogenous serine. To test this hypothesis, we checked the expression level of enzymes that catalyse the biosynthesis of serine in the liver of NASH patients, and it was observed that the expression levels of PHGDH, PSAT1, PSPH in serine synthesis pathway (SSP), and SHMT1 and SHMT2 enzymes were significantly downregulated (Supplementary Table 6).…”
Section: Reporter Metabolites Subsystems In Hmr Databasementioning
confidence: 64%
See 1 more Smart Citation
“…Taken together, the results suggest that the changes in the level of PS in the liver 47 as well as the relative increase in the homocysteine blood level 49 is caused by decreased level of endogenous serine. To test this hypothesis, we checked the expression level of enzymes that catalyse the biosynthesis of serine in the liver of NASH patients, and it was observed that the expression levels of PHGDH, PSAT1, PSPH in serine synthesis pathway (SSP), and SHMT1 and SHMT2 enzymes were significantly downregulated (Supplementary Table 6).…”
Section: Reporter Metabolites Subsystems In Hmr Databasementioning
confidence: 64%
“…Downregulation of CBS that catalyses the conversion of serine and homocysteine to L-cystathionine and upregulation of MTR that condensates homocysteine to methionine through the use of 5-methyl-THF indicate that there are metabolic changes around homocysteine in NASH patients. Notably, it has been earlier reported that the plasma homocysteine level can be used for diagnosing NASH and classifying steatosis and NASH patients 49 . It is not always straightforward to relate blood concentrations to gene expression levels of the involved enzymes, but our model-based analysis suggests a mechanistic explanation for this.…”
Section: Reporter Metabolites Subsystems In Hmr Databasementioning
confidence: 99%
“…Hyperhomocysteinemia is associated with steatosis presumably through induction of endoplasmic reticulum stress and activation of SREBPs leading to increased hepatic synthesis and uptake of triglycerides and cholesterol [194]. Indeed, hyperhomocysteinemia may be a suitable predictor of NASH [195]. Preliminary data demonstrates that betaine supplementation prevented chronic alcoholinduced steatosis and losses in the respiratory chain complexes, particularly subunits of Complex I and IV [196].…”
Section: Are Antioxidants Feasible Treatments For Fatty Liver Disease?mentioning
confidence: 99%
“…In hepatology, experimental data in transgenic mice deficient in homocysteine metabolism enzymes have shown the presence of severe liver steatosis with occasional steatohepatitis [43]. In human beings, many studies have found a correlation between homocysteine and steatosis or even NASH [44,45]. Some authors have suggested a discriminating threshold to differentiate simple steatosis from NASH.…”
Section: Discussionmentioning
confidence: 99%